PENGARUH DUKUNGAN SOSIAL, KUALITAS PENGAJARAN, DAN PENGEMBANGAN PROFESIONAL TERHADAP KETERAMPILAN MENGAJAR PADA GURU ANAK USIA DINI - Linda Ardiya Waroka; Sri Ratu Ratna Intan; Munadia; Annisa Putri; Ampun Bantali (CV. Lafadz Jaya, 2026)
Early childhood education (ECE) plays an important role in the development of children's character and skills. In Indonesia, ECE faces challenges such as a lack of social support and poor teaching quality. This study adopts a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to analyze data from 100 early childhood education teachers in Yogyakarta. The results show a positive relationship between Social Support, Professional Development, and Teaching Quality and Teaching Skills. The path coefficients indicate that social support has the most significant influence, followed by professional development. However, teaching quality shows poor path coefficients, suggesting the need for further evaluation and improvement. The R-squared value reached 74.7%, indicating that the model is significantly capable of explaining the variation in teaching skills. This research emphasizes the importance of building a supportive social environment and providing training opportunities for teachers. Teaching quality metrics need to be improved to support the development of teaching skills. This finding provides a strong foundation for better educational intervention strategies, ensuring every teacher has the necessary resources and support to optimize their teaching skills.